DISPOSITION EFFECT DALAM PEMBUATAN KEPUTUSAN INVESTASI OLEH KELOMPOK DAN INDIVIDU - Elsa Juliati; Dewi Candrawati (LPPM STIE YKPN Yogyakarta, 2023)
The purpose of this research is to analyze the influence of the disposition effect in decision making investment by groups and individuals and to determine the differences in disposition effects by groups and individuals in decision making investment. This research method uses a true experiment with posttest control group design. This experiment involved two treatments that is individuals and groups. The research population was students of STIE YKPN Yogyakarta with the number of samples collected were 40 subjects and the number that could be processed were 19 groups of subjects and 32 individual subjects. The analysis technique used in this research is logistic regression analysis and One Way ANOVA. The results of this research showed that the disposition effect in decision making investment by the group had significant influence (P = 0.009 <α = 0.05) and the disposition effect in decision making investment by individuals had significant influence (P = 0.011 <α = 0.05), but there is no difference in disposition effect by groups and individuals in decision making investment (P = 0.269> α = 0.05).